Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/am504985w
|View full text |Cite
|
Sign up to set email alerts
|

Biothiols as Chelators for Preparation of N-(aminobutyl)-N-(ethylisoluminol)/Cu2+ Complexes Bifunctionalized Gold Nanoparticles and Sensitive Sensing of Pyrophosphate Ion

Abstract: In this work, chemiluminescence (CL) reagent and catalyst metal ion complexes bifunctionalized gold nanoparticles (BF-AuNPs) with high CL efficiency were synthesized via an improved synthesis strategy. Biothiols, such as cysteine (Cys), cysteinyl-glycine (Cys-Gly), homocysteine (Hcy), and glutathione (GSH), instead of 2-[bis[2-[carboxymethyl-[2-oxo-2-(2-sulfanylethylamino)ethyl]amino]ethyl]amino]acetic acid (DTDTPA), were used as new chelators. N-(aminobutyl)-N-(ethylisoluminol) (ABEI) was used as a model of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 37 publications
1
24
0
1
Order By: Relevance
“…They often need to construct a CL interface to produce analytical signal. Earlier work demonstrated that CL functionalized nanomaterials such as CL reagent/metal ion (catalyst) bifunctionalized gold nanoparticles, , graphene oxide, and multiwalled carbon nanotubes are good interfaces for label-free bioassays. However, in most of cases, such CL functionalized nanomaterials need to be further immobilized on a carrier such as a microplate and an electrode to construct a CL interface for label-free bioassays so that the separation can be carried out after they react with recognition biomolecules and analytes in samples.…”
mentioning
confidence: 99%
“…They often need to construct a CL interface to produce analytical signal. Earlier work demonstrated that CL functionalized nanomaterials such as CL reagent/metal ion (catalyst) bifunctionalized gold nanoparticles, , graphene oxide, and multiwalled carbon nanotubes are good interfaces for label-free bioassays. However, in most of cases, such CL functionalized nanomaterials need to be further immobilized on a carrier such as a microplate and an electrode to construct a CL interface for label-free bioassays so that the separation can be carried out after they react with recognition biomolecules and analytes in samples.…”
mentioning
confidence: 99%
“…另外, 生物流体中 ATP, AMP, ADP 等干扰离子的 含量大约在 nmol•L -1 数量级, 要比 PPi 含量低, 而 Pi 却比 PPi 含量高 [29] . Cui 等 [37] Figure 7 Chemiluminescence sensing emsemble for PPi based on the mechanism of competitive coordination 等离子增强的荧光技术能够明显放大荧光信号, 提 高检测灵敏度 [38] . Ouyang 等 [45,46] .…”
Section: P Ounclassified
“…Recently, much attention has been paid to chemiluminescent (CL) functionalized nanomaterials, especially gold nanoparticles, in bioassays due to their good CL property, ease of self-assembly and good biocompatibility. At the beginning, luminol-type CL reagent functionalized gold nanoparticles (CF-GNPs) were synthesized using direct reduction methods. , CL reagent molecules were used to reduce HAuCl 4 to obtain GNPs and acted as stabilizers to be coated on the surfaces of GNPs. CF-GNPs with good CL activities as analytical probes and interfaces have been successfully applied to immunoassays and DNA assays. Afterward, to develop CF-GNPs with high CL efficiency, catalysts metal ions were further coated onto the surfaces of GNPs with the help of chelators to form gold nanoparticles bifunctionalized by CL molecules and metal complexes (BF-GNPs) with excellent CL efficiency. , However, it is very challenging to connect BF-GNPs with recognition elements like antibodies, aptamers, and DNA because of the high surface coverage fraction of BF-GNPs, limiting their applications in bioassays. Therefore, we wonder if it is possible to directly assemble catalysts metal ions onto the surfaces of antibody conjugated CF-GNPs to obtain an ideal analytical interface with high CL efficiency during the fabrication of immunosensors by virtue of blocker bovine serum albumin (BSA), since BSA contains amino and carboxyl groups and is ready to coordinate with metal ions, avoiding the use of additional chelators.…”
Section: Introductionmentioning
confidence: 99%
“…10−12 Afterward, to develop CF-GNPs with high CL efficiency, catalysts metal ions were further coated onto the surfaces of GNPs with the help of chelators to form gold nanoparticles bifunctionalized by CL molecules and metal complexes (BF-GNPs) with excellent CL efficiency. 13,14 However, it is very challenging to connect BF-GNPs with recognition elements like antibodies, aptamers, and DNA because of the high surface coverage fraction of BF-GNPs, limiting their applications in bioassays. Therefore, we wonder if it is possible to directly assemble catalysts metal ions onto the surfaces of antibody conjugated CF-GNPs to obtain an ideal analytical interface with high CL efficiency during the fabrication of immunosensors by virtue of blocker bovine serum albumin (BSA), since BSA contains amino and carboxyl groups and is ready to coordinate with metal ions, avoiding the use of additional chelators.…”
Section: Introductionmentioning
confidence: 99%